Diet, Screen Time, Physical Activity, and Childhood Overweight in the General Population and in High Risk Subgroups: Prospective Analyses in the PIAMA Birth Cohort - Alet H. Wijga; Salome Scholtens; Wanda J. E. Bemelmans; Marjan Kerkhof; Gerard H. Koppelman; Bert Brunekreef; Henriette A. Smit (Journal of Obesity)
Objective. To prospectively identify behavioral risk factors for childhood overweight and to assess their relevance in high risk sub groups (children of mothers with overweight or low education). Methods. In the PIAMA birth cohort (𝑛=3963), questionnaire data were obtained at ages 5 and 7 on “screen time”, walking or cycling to school, playing outside, sports club membership, fast food consumption, snack consumption and soft drink consumption. Weight and height were measured at age 8 years. Results. Screen time, but none of the other hypothesized behavioral factors, was associated with overweight (aOR 1.4 (CI: 1.2–1.6)). The adjusted population attributable risk fraction for screen time > 1 hr/day was 10% in the high risk and 17% in the low risk sub groups. Conclusion. Reduction of screen time to < 1 hr/day could result in a reduction of overweight prevalence in the order of 2 percentage points in both high and low risks sub groups.